The Effect of Physically Modification Process on Starch Characteristic and Resistant Starch Production from Four Varieties of Cassava (Manihot esculenta)) - Nazhrah Nazhrah; Elisa Julianti; Linda Masniary Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Resistant starch is a starch or starch degradation products that are not digested in the human digestive system so that the starch can escape digestion in the small intestine system but can be fermented by the natural microflora in the large intestine. Resistant starch has a positive impact on health, such as preventing the increase in blood glucose levels significantly. This research used cassava as raw material because it had functional properties i.e resistant starch content that can be obtained through the treatment process. The purpose of this research was to study the influence of physically modification process on the production of resistant starch and to determine the characteristics of the modified starch from four varieties of cassava. The physical process was done by autoclaving at 110oC and 121oC. The research was conducted in two phases, making the natural starch from four varieties of cassava starch and modification of starch. The physical and chemical characteristics of modified starch were tested including moisture, ash, protein, and fat content, pH value, pasting properties, starch granules shape and size, total sugars, starch, and resistant starch content. Modification treatment by autoclaving at 110oC produced the highest resistant starch content (36,78%) and modified starch from yellow tuber- cassava which is modified by autoclaving treatment 121oC) had the highest resistant starch content (53,22%). Keywords: Cassava, Modified Starch, Resistant Starch